PENGARUH INTENSITAS PENGAIRAN DAN DOSIS PUPUK MAJEMUK TERHADAP PERTUMBUHAN, PRODUKSI DAN MUTU TEMBAKAU MADURA DI KABUPATEN TUBAN - Elina; Nita, Istika; Nopriani, Lenny Sri; Andriyanto, Chandra; Nugroho, Prasetyo Adi (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Madurese tobacco (Nicotiana tabacum  L.) is a semi-aromatic tobacco that is very much needed by the Kretek cigarette industry, with the dominant cultivated varieties being Prancak-95 and Tarnyak. Madura tobacco production every year does not meet the market needs, so efforts to increase production through land extensification are one solution. The extensification of Madura tobacco land was carried out in Tuban Regency because it has suitable climatic conditions. This research aims to obtain the best irrigation and fertilization recommendations for the growth, production, and quality of Madurese tobacco in Tuban Regency. Madurese tobacco requires essential nutrients for its growth to produce good quality, such as nitrogen (N), phosphorus (P) and potassium (K), so it requires the addition of compound fertilizer. This research was carried out during the dry season in Tluwe Village, Soko District, Tuban Regency. This experiment used a Factorial Randomized Block Design consisting of 3 factors (variety P (Prancak-95) and T (Tarnyak), compound fertilizer dose 1 (100% fertilizer) and 2 (50% fertilizer), and irrigation intensity A (Water 100%). %) and B (Water 50%)) with 8 combinations and 3 repetitions, namely P1A, P1B, P2A, P2B, T1A, T1B, T2A, T2B. The research results showed that treatment of irrigation intensity and compound fertilizer had a significant effect on growth but no significant effect on production. The T1B treatment provided the highest average value for growth. P2B treatment produced the best quality Madurese tobacco physically and chemically (quality I), namely greenish/bright yellow color, elastic handle, very fresh aroma, nicotine content of 2.97%, and sugar content of 14.46%. Further research is recommended to be carried out with the addition of variations in fertilizer doses to obtain more optimal results for the growth, production, and quality of Madura tobacco.